Who Will Help to Strive Against the “Infodemic”? Reciprocity Norms Enforce the Information Sharing Accuracy of the Individuals - Li, Kehan; Xiao, Weiwei (Frontiers in Psychology, 2022)
In recent years, misinformation sharing has become the focus of public debate and academic research. We aim to explore whether individuals prefer to share accurate information or not, and discover what factors increase people’s preferences for sharing accurate information. Combining behavioral economics experiments and psychology experiments, we construct “an information search—information sharing—information feedback experiment” to examine individuals’ behavior of sharing accurate information and its influencing factors. A total of 210 students are recruited for the laboratory experiment. Our results show that when individuals can control the accuracy of the information they obtain through their efforts, they are more willing to share accurate information with others. We also find that positive feedback from information receivers can promote the accuracy of information shared by individuals, and this effect works through reciprocity norms. Individuals with higher reciprocity are more willing to share accurate information, especially in the treatment with the role of reciprocity norms enhanced by feedback. These findings indicate that individuals who are willing to obtain accurate information prefer to share information, and information feedback can enhance this preference through reciprocity norms. This study captures individuals’ behavior and preference characteristics with regard to the accuracy of the information they share in the era of highly developed network interaction.